Production of renewable glucose from oil palm frond bagasse by using sacchariseb C6 through enzymatic hydrolysis - Fatin Syazwana, Hashim (2017)
Lignocellulosic biomass (LCB) is the most abundant renewable biomass that gives high potential source in production of various beneficial products. Recently, oil palm crops are known as the most potential LCB which can be employed for sugar production. Normally, wastes from oil palm crops are used as animal feed but this is not the ideal economically valuable method of manipulating the wastes. Besides, the existence of wastes created disposal problems and often been disposed off by open burning that may lead to the environmental pollution. Therefore, oil palm frond (OPF) bagasse was introduced as a raw material in this study to maximize the utilization of oil palm waste. This study aims to characterize the composition of OPF bagasse before and after alkaline pretreatment and to screen and optimize the factors affecting enzymatic hydrolysis by using Sacchariseb C6 for glucose production. OPF bagasse was treated using alkaline pretreatment and sodium hydroxide used as a solvent before proceeding with enzymatic hydrolysis using Sacchariseb C6. During pretreatment process, cellulosic biomass structure will be altered and delignification occurred which make cellulose more accessible to the subsequent enzymatic hydrolysis process by converting it into simple sugars. Response Surface Methodology (RSM) was employed to screen and optimize the enzymatic hydrolysis condition. Characterization of raw OPF bagasse produced 40.7 % glucan, 26.1 % xylan, 4.5 % extractives, 26.2 % lignin and 1.8 % ash. Meanwhile, pre-treated OPF bagasse composed of 61.4 % glucan, 20.4 % xylan, 0.3 % extractives, 13.3 % lignin and 1.3 % ash. In factorial analysis study, the best enzymatic hydrolysis condition yielded 33.01 ± 0.73 g/L of glucose when performed at 200 rpm of agitation speed, 60 FPU/g of enzyme loading, 4% (w/v) of glucan loading, temperature at 55 °C and 72 hours of reaction time. In central composite design (CCD), the optimum condition for enzymatic hydrolysis was obtained at 50 ℃ for 87.93 hours of hydrolysis time which produced 41.11 ± 0.11 g/L of glucose. Overall, enzymatic hydrolysis of OPF bagasse by using Sacchariseb C6 has high potential for production of glucose which later can be utilized for various industrial application to produce valuable value-added products.